Identification method of thief zones in carbonate reservoirs based on the combination of static and dynamic data: A case study from the Cretaceous Mishrif Formation in the H oilfield, Iraq - Li, Ruixue; Deng, Hucheng; Fu, Meiyan; Hu, Lanxiao; Xie, Xinhui; Zhang, Liying; Guo, Xiaobo (Frontiers in Energy Research, 2023)
Carbonate reservoir usually has a strong heterogeneity. The zones with relatively high permeability will form a channel where fluids can easy flow through. These channels are called thief zones. Thief zones lead to obvious effects on oil or gas production, e.g., a high oil recovery rates at the early stage of the exploitation or an early water breakthrough during the later stage of water flooding development. Therefore, it is essential to have a precise identification of thief zones in carbonate reservoirs. In this research, a simple approach to identify thief zones based on reservoir permeability gathered from well logging is developed. The thief zones are first identified at wells based on the lower limit value of the thief-zone permeability. This value is determined based on the dynamic production data, making that the thief zones identified by applying this criterion can reflect the production characteristics. Then, a zonal inter-well recognition method is adopted to identify the connectivity and distributions of thief zones in the regions far away from the well. This method is applied to identify thief zones for Cretaceous Mishrif formation in H oilfield, Iraq. The reliability of the identification results is tested by the well-group injection test. The distributions of thief zones in the study region are discussed. In the study region, 12 members developed thief zones, while 2 members (i.e., MC1-3 and MC2-2) do not develop thief zones. Especially, there are 5 members have a high level of thief-zone development. They are MB1¬-2C, MB2¬-1, MB2¬-2, MC2¬-3, and MC3¬-2, respectively. Comparing the distribution of thief zones with that of sedimentary microfacies, it can conclude that the thief-zone development is mainly controlled by the sedimentary microfacies and prefers to appear in high-energy shoal.